Enseignement de l’hétérographie distinctive et genèse orthographique au cycle 2 - Pierre Sémidor (Recherches en Éducation)
Daily and repetitive activities to accustom students to the reading and writing code tend to be the norm for children in their 1st years at school. We observe teachers providing discursive orthographic opportunities in their classes in which recurrent spelling activities are offered to students. Within these activities, the focus is on the segmentation of phrases into words and distinct heterographology. This systematic approach is at the base of orthography and could have an impact on the writing patterns of students. Incorporating such orthographic writing patterns could therefore lead to an increase in knowledge and would facilitate the integration of such knowledge.